Reality is broken why games make us better and how they can change the world - McGonigal, Jane. (New York Penguin Press, 2011)
Visionary game designer Jane McGonigal shows how we can harness the power of computer games to solve real-world problems and boost global happiness, since her research suggests that gamers are expert problem solvers and collaborators because they regularly cooperate with other players to overcome daunting virtual challenges.
Includes bibliographical references (p. [364]-378) and index.
Keywords: Computer games -Social aspects